1981
DOI: 10.1136/bmj.283.6296.881
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension and fenfluramine

Abstract: Pulmonary hypertension developed in two women who had been taking fenfluramine for over eight months for weight reduction. On withdrawing the drug symptoms and electrocardiographic evidence of pulmonary hypertension disappeared in both cases. In one patient, however, the evidence recurred after rechallenge with fenfluramine.These findings are strong evidence that fenfluramine may cause pulmonary hypertension. Hence any patient taking the drug should report immediately any deterioration in exercise tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(37 citation statements)
references
References 7 publications
(1 reference statement)
0
35
0
2
Order By: Relevance
“…In the early 1980s, the first descriptions of a possible relationship between the use of fenfluramine derivatives and PAH were published [8]. Following this, a retrospective study [9] reinforced the possible role of fenfluramine derivatives as risk factors for PAH development and the results of the International Primary Pulmonary…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 1980s, the first descriptions of a possible relationship between the use of fenfluramine derivatives and PAH were published [8]. Following this, a retrospective study [9] reinforced the possible role of fenfluramine derivatives as risk factors for PAH development and the results of the International Primary Pulmonary…”
mentioning
confidence: 99%
“…The fact that the epidemic started 2 yrs after aminorex fumarate became commercially available and disappeared 2 yrs after the drug was withdrawn, allowed the recognition of temporal and geographic relationships between the use of the drug and PAH development [6]. Although this clearly indicated a role as a risk factor, the clinical course of aminorex-associated PAH was not conclusively different from idiopathic PAH (IPAH, formerly known as primary pulmonary hypertension), despite later results suggesting a better survival in the first group [7].In the early 1980s, the first descriptions of a possible relationship between the use of fenfluramine derivatives and PAH were published [8]. Following this, a retrospective study [9] reinforced the possible role of fenfluramine derivatives as risk factors for PAH development and the results of the International Primary Pulmonary…”
mentioning
confidence: 99%
“…It has been clearly demonstrated that the risk of developing PAH is increased after exposure to anorexigens, such as aminorex and fenfluramine derivatives [12,[39][40][41][42]. For example, SOUZA et al [40] have shown that fenfluramineassociated PAH shares similar clinical, functional, haemodynamic and genetic characteristics with idiopathic PAH.…”
Section: Toxic and Tobacco Exposurementioning
confidence: 99%
“…In the 1960's, PPH was linked to the use of the appetite suppressant aminorex. 13,28 More recently, PPH has been reported to be linked to the chronic use of dexfen and fen¯ura-mine 10,11,14,15,29 Moreover, exposure to phentermine alone has resulted in reported cases of PPH. 30 ± 32 Serotonin has long been thought to play a role in the development of PPH.…”
Section: Primary Pulmonary Hypertensionmentioning
confidence: 99%